Title Characteristics and Citations in Economics - Matthias Gnewuch; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2016)
We investigate the relationship between article title characteristics and citations in economics using a large data set from Web of Science. Our results suggest that articles with a short title that also contains a non-alphanumeric character achieve a higher citation count.
Keywords: A12; A14; 330; articles; title characteristics; citations; non-alphanumeric characters; title length